Ab Initio Investigation on the Magnetic Moments, Magnetocrystalline Anisotropy and Curie Temperature of Fe2P-Based Magnets - Stephan Erdmann; Halil İbrahim Sözen; Thorsten Klüner (Magnetism, 2025)
Permanent magnetic materials are essential for technological applications, with the majority of available magnets being either ferrites or materials composed of critical rare-earth elements, such as well-known Nd2Fe14B. The binary Fe2P material emerges as a promising candidate to address the performance gap, despite its relatively low Curie temperature <semantics>TC</semantics> of 214 K. In this study, density functional theory was employed to investigate the effect of Si and Co substitution on the magnetic moments, magnetocrystalline anisotropy energy (MAE) and Curie temperature in <semantics>Fe2−y</semantics>CoyP1−xSix compounds. Our findings indicate that Si substitution enhances magnetic moments due to the increase in 3f-3f and 3f-3g interaction energies, which also contribute to higher <semantics>TC</semantics> values. Conversely, Co substitution leads to a reduction in magnetic moments, attributable to the inherently lower magnetic moments of Co. In all examined cases of different Si concentrations, such as hexagonally structured <semantics>Fe2−y</semantics>CoyP, <semantics>Fe2−y</semantics>CoyP0.92Si0.08 and <semantics>Fe2−y</semantics>CoyP0.84Si0.16, Co substitution increases the Curie temperatures by augmenting 3g-3g exchange interaction energies. Both Si and Co substitutions decrease the magnetocrystalline anisotropy energy, resulting in the loss of the easy magnetization direction at higher Co contents. However, higher Si concentrations appear to confer resilience against the loss. In summary, Si and Co substitutions effectively modify the investigated magnetic properties. Nonetheless, to preserve a high MAE, the extent of substitution should be optimized.